PENGARUH GAME NUMERASI (GANU) MENGGUNAKAN PENDEKATAN STEAM TERHADAP KEMAMPUAN NUMERASI ANAK USIA 5-6 TAHUN - Fauziyah, Cicik; Rakhmawati, Nur Ika Sari (Universitas Bhinneka PGRI, 2023)
The purpose of this research is to examine the effect of the Numeracy Game (GANU) using the STEAM approach on the numeracy skills of children aged 5-6 years old. This research method employs a quantitative research design with a quasi-experimental design known as the nonequivalent control group design. The subjects of this study consist of 40 children from 2 kindergartens in Sukolilo District, Surabaya. Data was collected through non-participant observation techniques. The data analysis in this study utilized independent t-test. The research findings indicate that the Numeracy Game (GANU) learning with the STEAM approach yielded a sig. value of 0.000 or (2-tailed) 0.05, which means that the null hypothesis is rejected, and the alternative hypothesis is accepted. Therefore, it can be concluded that there is an influence of the STEAM approach using the Numeracy Game (GANU) in enhancing the numeracy skills of children aged 5-6 years old.